Grain sorghum desiccation: Impacts on plant and grain dry‐down. Issue 4 (25th November 2021) - Ballagh, Anna; Kezar, Sarah; Harris, Stephen C.; Lofton, Josh
Abstract: Desiccants have been used in many crops to aid in late‐season dry‐down, hasten harvest, and improve harvest efficiency. Glyphosate, the primary desiccant used in grain sorghum [ Sorghum bicolor  (L.) Moench] production, can be effective at drying the crop but has been noted to have issues completely desiccating plants. The objective of this study was to evaluate the impact of various desiccant products on grain sorghum dry‐down and yield. Field trials were conducted at Goodwell and Stillwater, Oklahoma, in 2017 and 2018. Five desiccation treatments were applied at approximately 30% seed moisture, with dry‐down time, grain yield, and foreign material evaluated in this study. It was found that the use of desiccants aided in a more rapid and greater dry‐down of the sorghum plant in both Goodwell and Stillwater locations, with the glyphosate and glyphosate/saflufenacil applications showing the greatest drydown. As opposed to plant moisture, grain moisture was not consistently influenced by desiccation treatments. Due to mild late‐season weather, grain yield was increased from the use of desiccants at the Stillwater location primarily as a result of increased harvest efficiency. Overall, it was found that both glyphosate and the combination of glyphosate with saflufenacil provide better dry‐down compared with saflufenacil, carfentrazone, and sodium chlorate desiccants alone. In most sorghum production systems, glyphosate would be adequate in terms of dry‐down and control of late‐season weeds; however, if saflufenacil were to become labeled, it could provide an option for growers in certain production systems, such as those with problematic weeds. Core Ideas:  Desiccation improved dry‐down of plant biomass but not grain.  Grain yield was improved with the use of desiccants.  Freeze events shortly after application lowered the benefit of desiccants.  Glyphosate and glyphosate/saflufenacil resulted in a lower plant moisture and quicker dry‐down.